Mass-Removal and Mass-Flux-Reduction Behavior for Idealized Source Zones with Hydraulically Poorly-Accessible Immiscible Liquid - Brusseau, M.L. (2008)
A series of flow-cell experiments was conducted to investigate aqueous dissolution and mass-removal behavior for systems wherein immiscible liquid was non-uniformly distributed in physically heterogeneous source zones. The study focused specifically on characterizing the relationship between mass flux reduction and mass removal for systems for which immiscible liquid is poorly accessible to flowing water. Two idealized scenarios were examined, one wherein immiscible liquid at residual saturation exists within a lower-permeability unit that resides in a higher-permeability matrix, and one wherein immiscible liquid at higher saturation (a pool) exists within a higher-permeability unit adjacent to a lower-permeability unit. The results showed that significant reductions in mass flux occurred at relatively moderate mass-removal fractions for all systems. Conversely, minimal mass flux reduction occurred until a relatively large fraction of mass (>80%) was removed for the control experiment, which was designed to exhibit ideal mass removal. In general, mass flux reduction was observed to follow an approximately one-to-one relationship with mass removal. Two methods for estimating mass-flux-reduction/mass-removal behavior, one based on system-indicator parameters (ganglia-to-pool ratio) and the other a simple mass-removal function, were used to evaluate the measured data. The results of this study illustrate the impact of poorly accessible immiscible liquid on mass-removal and mass-flux processes, and the difficulties posed for estimating mass-flux-reduction/mass-removal behavior.